Dynamic characteristics improvement of the single screw compressor with odd-grooves screw rotor. (December 2021) - Peng, Chengyu; Wu, Weifeng; Zhang, Zhao; Xie, Jia; Feng, Quanke; He, Zhilong
Highlights: A novelty screw rotor structure is proposed to smooth the compressed gas-force torque. A novelty method is presented to calculate the gas force and torque of screw rotor. The compressed gas-force torque of the screw rotor is contrastively analyzed. The influences of the pressure difference and compression capacity are discussed. The load brought by the novelty structure on the bearing is investigated. Abstract: Recently, the single screw compressor (SSC) has been applied in the low-temperature heat pump system with the purpose of achieving higher system efficiency. However, the traditional SSC with even-grooves screw rotor behaves high torque fluctuation to the motor, thanks to its work synchronously and doubled compressed gas-induced torque on the screw rotor axis. It is more serious in the low-temperature heat pump system because of the higher pressure ratio. In this paper, an odd-grooves screw rotor design is proposed to smooth the compressed gas-induced torque on the screw rotor axis, by arranging the two compression chambers work alternatively. A dynamic model for the screw rotor is established to calculate the gas force and the gas-induced torque on screw rotors under different working conditions. The results show that the odd-grooves screw rotor design can remarkably reduce the gas-induced torque fluctuation of the SSC. Meanwhile, the maximal load on the bearing caused by the odd grooves design could be controlled below the maximum allowable load of the bearing.